2014
DOI: 10.11604/pamj.2014.19.168.5166
|View full text |Cite
|
Sign up to set email alerts
|

An association of vertebral breast cancer metastasis and multiple myeloma, revealed by a spinal cord compression

Abstract: Authors describe the case of a patient with breast cancer and multiple myeloma as the second metachronous disease responsible for spinal cord compression. Synchronous occurrence of bone marrow breast cancer disease and multiple myeloma has not been described in the literature, as in this case. By presenting this case, we point to possible association between both diseases and the possible factors involved in the development of second malignant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Sakai et al [11] reported an association between multiple myeloma with clear cell renal carcinoma and emphasized the possible role of growth factors like IL-6. Kherfani et al [12] reported a synchronous hormone receptor-positive breast cancer and multiple myeloma case with the involvement of thoracic and lumbar spinal cord. Sehgal et al [13] reported a case of prostate adenocarcinoma and multiple myeloma with synchronous infiltration of bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Sakai et al [11] reported an association between multiple myeloma with clear cell renal carcinoma and emphasized the possible role of growth factors like IL-6. Kherfani et al [12] reported a synchronous hormone receptor-positive breast cancer and multiple myeloma case with the involvement of thoracic and lumbar spinal cord. Sehgal et al [13] reported a case of prostate adenocarcinoma and multiple myeloma with synchronous infiltration of bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction may be challenging by cytomorphology alone [ 17 ]. Kherfani et al reported a case of spinal cord compression from concurrent multiple myeloma and metastatic breast cancer in the same vertebra [ 18 ]. Al-Said Ali et al reported synchronous diagnosis of multiple myeloma and breast cancer on initial presentation similar to our case in 2009 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are a number of reports describing the relationship between anthracyclines and increased risk of acute myeloid leukemia in women with breast cancer (4, 5). In addition, by a PubMed search, we found few reports concerning patients with multiple myeloma mimicking bone metastases of breast cancer (6, 7) or association of vertebral breast cancer metastasis and multiple myeloma (8).…”
Section: Introductionmentioning
confidence: 99%